1969
DOI: 10.1161/01.res.24.5.639
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Actions of Lidocaine on Canine Ventricular Muscle and Purkinje Fibers

Abstract: Isolated canine papillary muscles with attached false tendons were perfused with Tyrode's solution containing lidocaine. Transmembrane action potentials of ventricular muscle fibers and Purkinje fibers were recorded with glass microelectrodes. Repolarization of Purkinje fibers was accelerated by lidocaine but that of ventricular muscle fibers was unaffected. The maximum rate of rise of the action potential of Purkinje fibers decreased only at 50.0 mg/ liter lidocaine; that of ventricular muscle fibers was unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(52 citation statements)
references
References 55 publications
(62 reference statements)
5
45
2
Order By: Relevance
“…The highest concentration of lignocaine studied significantly shortened the human ventricular action potential duration at 50 and 90% repolarization levels, the effect being similar in both [K + ]. These results are in agreement with those obtained in both canine and rabbit ventricular muscle (Davis & Temte, 1969;Singh & Vaughan Williams, 1971 Davis & Temte (1969). This prolongation of ARP, independent of a lengthening in APD, may be explained by the ability of lignocaine to prolong the reactivation kinetics of the rapid inward sodium current (Chen et al, 1975).…”
Section: Discussionsupporting
confidence: 89%
“…The highest concentration of lignocaine studied significantly shortened the human ventricular action potential duration at 50 and 90% repolarization levels, the effect being similar in both [K + ]. These results are in agreement with those obtained in both canine and rabbit ventricular muscle (Davis & Temte, 1969;Singh & Vaughan Williams, 1971 Davis & Temte (1969). This prolongation of ARP, independent of a lengthening in APD, may be explained by the ability of lignocaine to prolong the reactivation kinetics of the rapid inward sodium current (Chen et al, 1975).…”
Section: Discussionsupporting
confidence: 89%
“…However, the electrophysiological effect of lignocaine on isolated canine Purkinje fibres and ventricular muscle have been studied in detail (Davis & Temte, 1969;Bigger & Mandel, 1970a, b). Its effects have been compared with those of propranolol (Davis & Temte, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that lidocaine at therapeutic concentrations suppresses normal automaticity and delayed afterdepolarizations. 22,23 The effects of the drug matrix on mechanisms for normal and abnormal impulse initiation have been studied extensively, as have its effects on conduction.9-12,18,23,26 However, knowledge of its actions on cell coupling, on passive membrane properties, and on threshold for excitability are incomplete. Needless to say, such information would be valuable in furthering our understanding of the actions of the drugs in the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The Purkinje fibers were impaled with 3 M KCIfilled glass microelectrodes having tip resistances of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Mfl. Attempts were made to impale the site of earliest impulse initiation, at which the slope of phase 4 and phase 0 merged smoothly in the typical configuration of a pacemaker fiber.…”
Section: Methodsmentioning
confidence: 99%